Study on the use of Contraceptive Devices For Coupleso Childbearing Age in Kedampul Hamlet, Duwet Village Tumpang District, Malang Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Kedampul Orchard is a Family Planning village formed by National Population and Family Planning Boards . The problems found in this region are high fertility but the smallest number of acceptors. This research needs to be able to determine the socio-economic and demographic conditions that affect fertility. This research is a survey research with a correlational approach. Sampling using proportional random sampling technique. The results of statistical tests of injectable contraception (sig = 0.000) were more effective than those with pills (sig = 0.045). The results of this study indicate that the factors that influence fertility are age when using contrast devices, while education, employment, and age at first marriage do not affect fertility.